String-corrected dilatonic black holes in dimensions - Moura, Filipe (2011)
We solve the dilaton field equation in the background of a spherically symmetric black hole in bosonic or heterotic string theory with curvature-squared corrections in arbitrary d spacetime dimensions.We then apply this result to obtain a spherically symmetric black hole solution with dilatonic charge and curvature squared corrections in bosonic or heterotic string theory compactified on a torus. For this black hole, we obtain its free energy, entropy, temperature, specific heat, and mass.